Gender Politics in Lithuania. A Case of Gender-Based Violence against Womean in the Family - Reingardienė, Jolanta (Sociologija. Mintis ir veiksmas, 2002)
One of the main objectives of this article is to discuss the different social variables of soviet past as well as post-soviet present in relation to a continued form of direct and intended social control in. Lithuania - gender based violence against women in the family. It starts with a cursory review of women's roles and opportunities in the context of shifting boundaries of the public/private dichotomy and soviet egalitarian ideology followed by the discussion of the re-traditionalization process and its implications for family life and gender-based violence within it. The way gender was organized under the socialism figures importantly in all aspects of family interaction and organization during the last decade of democratization. The way the gender equality was legislated served to reinforce the significance of gender difference even while ostensibly undermining it. The further analysis includes a brief discussion of women 's attitudes towards gender based violence as they were revealed in the survey on the social context of women abuse in Lithuanian families that was carried out in Lithuania in May, 2000. The survey was completed using a direct structured interview method. It represents the opinion of all Lithuanian women within the age group from 18 to 74 years. Sample size is 517 respondents. Women included in the survey were selected using multilevel random sampling procedure. The response rate of the survey was 66.3%.
Keywords: gender; public and private spheres; post-Soviet Lithuania; violence in the families